2004
DOI: 10.2343/geochemj.38.623
|View full text |Cite
|
Sign up to set email alerts
|

Silver in the Pacific Ocean and the Bering Sea

Abstract: Detailed vertical profiles of dissolved Ag in the Bering Sea, the central North and South Pacific and the Southern Ocean have been present here. These profiles are comparable to our previous report in the western North Pacific, the Okhotsk Sea and the Japan Sea (Zhang et al., 2001). There is a systematic enrichment of Ag concentrations in the deep waters (North Atlantic < South Atlantic < South Pacific < North Pacific), which is parallel with the distributions of dissolved Si and consistent with the route of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…7a). A linear relationship was also obtained in the South and equatorial Pacific, with a slope higher than in the Atlantic and much greater concentrations in the surface waters (Zhang et al, 2004). It is thought that the Ag distribution is primarily controlled by uptake by diatoms with subsequent dissolution at depth of biogenic opal (Kramer et al, 2011).…”
Section: The Silver and Silicic Acid Relationshipmentioning
confidence: 78%
See 2 more Smart Citations
“…7a). A linear relationship was also obtained in the South and equatorial Pacific, with a slope higher than in the Atlantic and much greater concentrations in the surface waters (Zhang et al, 2004). It is thought that the Ag distribution is primarily controlled by uptake by diatoms with subsequent dissolution at depth of biogenic opal (Kramer et al, 2011).…”
Section: The Silver and Silicic Acid Relationshipmentioning
confidence: 78%
“…Similarly, low dissolved Ag concentrations were recorded in the deep waters of the southeastern Atlantic (Flegal et al, 1995). In fact, it is possible that there is a systematic enrichment of Ag in the deep waters from the North Atlantic towards the North Pacific along the global ocean deep circulation pathway (Zhang et al, 2004). Deep Ag distributions may hence further reflect water mass ages and long-term mixing of deep waters.…”
Section: Imprints Of the Continental Margin-open Ocean Exchanges And mentioning
confidence: 94%
See 1 more Smart Citation
“…This hypothesis is supported by culture experiments in the laboratory that show that Ag can be actively incorporated by organisms, notably diatoms [ Reinfelder and Fisher , 1991; Fisher and Wente , 1993; Lee and Fisher , 1994]. However, the relationship between Ag and Si is nonlinear (i.e., dissolved Ag increases more slowly than Si with water depth) [ Zhang et al , 2001, 2004; Ranville and Flegal , 2005]. This may be the result of relatively slower regeneration of Ag [ Zhang et al , 2001] or it may suggest that the distribution of dissolved Ag is affected by processes other than simple biological uptake in surface waters and regeneration at depth.…”
Section: Discussionmentioning
confidence: 96%
“…Dissolved Ag exhibits a nutrient‐type depth profile in the ocean (i.e., depleted in surface waters and increasing concentration with water depth) similar to that of dissolved Cu [ Martin et al , 1983] and Si [ Flegal et al , 1995; Rivera‐Duarte et al , 1999; Ndung'u et al , 2001; Zhang et al , 2001; Zhang et al , 2004; Ranville and Flegal , 2005]. The concentration of dissolved Ag in deep waters also increases from the northern Atlantic Ocean (2.8 to 4.0 pmol, Rivera) [ Rivera‐Duarte et al , 1999] to the North Pacific Ocean (40.9–55.0 pmol) [ Zhang et al , 2004] and Bering Sea (104.5 pmol) [ Zhang et al , 2004], as is typical for nutrient‐type elements. On the basis of the similarity between the dissolved Ag and Si profiles [ Flegal et al , 1995; Zhang et al , 2001] and work in Saanich Inlet, British Columbia, Canada, it has been suggested that Ag is incorporated into diatom frustules and later released as these as these particles dissolve [ Kramer , 2006].…”
Section: Discussionmentioning
confidence: 99%